Innovative Approaches in the Development of Kazakhstan Railway Industry - MUFTIGALIYEVA, Aliya; KUANGALIYEVA, Tursynzada; IBYZHANOVA, Aizhan; MIRZAGELDY, Kemel; KAIGORODZEV, Aleksandr; BAIGABULOVA, Kulyash; SARGAEVA, Natalia (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
In modern conditions the innovative development of the country – the main goal of the state policy in the field of science and technology. The most important direction of the state innovation policy is the formation of the national innovation system. In cyclically developing economy emerging from the structural crisis national economic policies contribute to the formation of a new type of industry: on the stage of economic growth – to its development and strengthening, on the stage of stabilizing – it is aimed at the realization of the existing potential. Depending on the stage of its development, economic policy provides any support for the existing structure of the industry, or to the formation of the branch structure of a new type. State innovation policy is mainly aimed at creating favorable economic, institutional, legal, informational, social and psychological conditions for the implementation of innovative processes. These conditions and the variety of methods of formation of innovation policy define the basic strategic directions of state support for innovation. In the article the questions of strategic management were shown, the features of the formation and development of the railway industry of the Republic of Kazakhstan. Special attention was attended to the assessment of the strategic management of the real economy sector.